2020
DOI: 10.1186/s12884-020-03248-5
|View full text |Cite
|
Sign up to set email alerts
|

Which is better for mothers and babies: fresh or frozen-thawed blastocyst transfer?

Abstract: Background In recent years, there have been many reports on the pregnancy outcomes of fresh blastocyst transfer (BT) and frozen-thawed BT, but the conclusions are controversial and incomplete. To compare the pregnancy outcomes, maternal complications and neonatal outcomes of fresh and frozen-thawed BT in the context of in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) cycles, we conducted a meta-analysis. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Some studies suggest that high oestrogen levels may lead to histological changes in the endometrium and could influence gene expression, which could affect embryo implantation and placental development, resulting in complications such as LBW ( 15 18 ). Analysis of neonatal outcomes from frozen embryo transfer (FET) cycles seems to be an alternative option because FET does not require high oestrogen levels to stimulate ovulation, keeping the endometrium conducive to early embryo development and implantation ( 19 ). Two recent studies analysed whether maternal age had an effect on neonatal birth weight from FET cycles and found that maternal age did not affect birth weight ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that high oestrogen levels may lead to histological changes in the endometrium and could influence gene expression, which could affect embryo implantation and placental development, resulting in complications such as LBW ( 15 18 ). Analysis of neonatal outcomes from frozen embryo transfer (FET) cycles seems to be an alternative option because FET does not require high oestrogen levels to stimulate ovulation, keeping the endometrium conducive to early embryo development and implantation ( 19 ). Two recent studies analysed whether maternal age had an effect on neonatal birth weight from FET cycles and found that maternal age did not affect birth weight ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the neonatal outcomes of FET, most studies have shown that there is no significant difference in the incidence of neonatal mortality or neonatal malformations between fresh and FET oocytes [ 3 ]. A meta-analysis conducted by Yang et al showed that FET had no significant correlation with neonatal organ system malformations and that FET did not increase the risk of neonatal organ system malformations [ 17 ].…”
Section: Discussionmentioning
confidence: 99%